Excitation of edge plasma instabilities and their role in pedestal saturation in the HL-2A tokamak. (20th April 2016) - Zhong, W L; Zou, X L; Shi, Z B; Duan, X R; Xu, Y; Xu, M; Chen, W; Jiang, M; Yang, Z C; Zhang, B Y; Shi, P W; Liu, Z T; et al.
Abstract: In HL-2A, the characteristics of the edge plasma instabilities and their effects on the dynamical evolution of the pedestal in H-mode plasmas have been investigated. In the edge pedestal region with steep pressure gradient, a quasi-coherent mode (QCM) has been observed in density fluctuations with a frequency range of 50–100 kHz. It appears during the edge localized mode (ELM)-free period after the L–H transition and prior to the first ELM. A threshold in the pedestal density gradient has been identified for the excitation of this mode. The QCM can also be observed during inter-ELM periods. It is excited early in the inter-ELM period, and disappears when the ELM onset starts. The radial wave-number of the mode is estimated with two radially separated reflectometers. It shows that the mode is radially propagating inward. The poloidal wave number estimated with the Langmuir probes is k θ ~ 0.43 cm −1 . The mode propagates poloidally in the electron diamagnetic direction in the plasma frame. The toroidal mode number, deduced from Mirnov signals, is n ~ 7. The corresponding poloidal mode number is m ~ 21 according to the local safety factor value. The analysis for the dynamical evolution of the pedestal during the ELM cycle clearly shows that the mode is excited before the ELM onset. During and after the ELM crash, the mode disappears. It suggests that the QCM is driven by the pedestal density gradient, and the mode in return regulates the pedestal density evolution.